2021
DOI: 10.1101/gr.275939.121
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of human and mouse ALS astrocytes reveals multi-omic signatures of inflammatory reactive states

Abstract: Astrocytes contribute to motor neuron death in amyotrophic lateral sclerosis (ALS), but whether they adopt deleterious features consistent with inflammatory reactive states remains incompletely resolved. To identify inflammatory reactive features in ALS human induced pluripotent stem cell (hiPSC)–derived astrocytes, we examined transcriptomics, proteomics, and glutamate uptake in VCP-mutant astrocytes. We complemented this by examining other ALS mutations and models using a systematic meta-analysis of all publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 69 publications
4
32
0
Order By: Relevance
“…This could serve as a protective mechanism at first but becomes toxic over time due to impaired homeostasis. These ALS astrocytes up-regulate inflammatory signaling and are seen to reduce its supportive actions to neurons [ 90 ].…”
Section: Major Participants In Astrocytic Glutamatergic Transmission ...mentioning
confidence: 99%
“…This could serve as a protective mechanism at first but becomes toxic over time due to impaired homeostasis. These ALS astrocytes up-regulate inflammatory signaling and are seen to reduce its supportive actions to neurons [ 90 ].…”
Section: Major Participants In Astrocytic Glutamatergic Transmission ...mentioning
confidence: 99%
“…Over the past years, multiple studies from independent laboratories have demonstrated that hiPSC modeling is a powerful tool for uncovering the role of astrocytes in CNS diseases, including AD ( Oksanen et al, 2017 ; Preman et al, 2021 ; de Leeuw et al, 2022 ), Parkinson’s disease ( di Domenico et al, 2019 ; de Rus Jacquet et al, 2021 ; Ramos-Gonzalez et al, 2021 ; Russ et al, 2021 ; Trudler et al, 2021 ) and amyotrophic lateral sclerosis ( Birger et al, 2019 ; Zhao et al, 2020 ; Szebényi et al, 2021 ; Ziff et al, 2021 ; Giacomelli et al, 2022 ). Developing human models is particularly critical since such diseases cannot be fully recapitulated in animal systems and thus require multiple integrated approaches (i.e., combination of human and animal studies) to understand their pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Because only a low number of samples were evaluated, this type of correlations should be further explored in studies analyzing a higher number of patients. However, most of the studies with patient cells also involved few cell lines and had a scientific impact [ 19 , 29 , 61 , 62 , 63 ]. The phenotypic variability observed in the present study between ALS iAstrocyte lines suggests that it may be useful in the stratification and subcategorization of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes were shown to release toxic factors and to have a key role in MN degeneration in both fALS and sALS patients [ 6 , 7 , 99 , 100 ]. Astrocyte-aberrant reactive features involving a decrease in GFAP and GLT-1 levels, an increased proliferative capacity, and an elevated expression of the Cx43 and S100B signature [ 20 , 21 ], together with inflammatory astrocytic markers [ 36 , 61 ], were identified in rodent and human ALS models. However, whether these markers are differently presented by fALS and sALS iAstrocytes was never investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation